The Times Literary Supplement historical archive, 1902-2019 - Gale (Firm) ([Farmington Hills, Mich.] : Gale Cengage Learning., 2010)
"Since 1902, the Times Literary Supplement has forged a reputation for fine writing, literary discoveries and insightful debate. The TLS has attracted the contributions of the world's most influential writers and critics, from T.S. Eliot and Virginia Woolf in the 1920s and 30s to A.N. Wilson and Christopher Hitchens in the 1990s and 2000s. The complete run of the TLS from 1902-2012 is now available online as the Times Literary Supplement Historical Archive, 1902 - 2012. The TLS Historical Archive, 1902-2012 is the improved and expanded new edition of the TLS Centenary Archive. This new edition enables users to full-text search 153,000 pages of the TLS from 1902 to 2012 and discover a wealth of content in approximately 315,000 articles.
The value of the TLS Historical Archive lies in its extensive cross-disciplinary reach, as the only literary weekly to offer comprehensive coverage of the latest and most important publications in multiple languages, across all areas of the humanities and social sciences. This unique digital collection offers thousands of book reviews - fiction and nonfiction, poetry, and covers every area of the visual and performing arts including film reviews, plays reviews and reviews of exhibitions, opera and theatre. It contains topical essays and criticism in the areas of science and medicine; art and architecture; history, music and religion; politics, economics and philosophy; exploration and sport; as well as engineering and town planning.""--Publisher description.
Title from advanced search screen (viewed May 2, 2012)
Database coverage: 1902 to 2014.
Mode of access: World Wide Web.
Absorbed TLS, the Times literary supplement centenary archive.
Keywords: Books -- Great Britain -- Reviews -- Indexes; Books -- Reviews -- Periodicals; Books -- Reviews -- Databases